Comparison study of indoor/outdoor experiments of a photovoltaic thermal PV/T system containing SiC nanofluid as a coolant. (15th May 2018) - Al-Waeli, Ali H.A.; Chaichan, Miqdam T.; Kazem, Hussein A.; Sopian, K.; Ibrahim, Adnan; Mat, Sohif; Ruslan, Mohd Hafidz
Abstract: Solar energy technology has been evolving for the better part of the last decade. Worldwide innovation and support have created an alternative energy source that is helping to battle climate change. Photovoltaic thermal (PV/T) converters use various working fluids. Silicon carbide (SiC) nanofluid is employed in this study in the cooling application of a PV/T system. The aim of this study is to assess and evaluate the performance of PV/T collectors when running a SiC nanoparticle dispersed in water as the base fluid for both indoor and outdoor systems. The performance assessment includes thermal, electrical and combined PV/T efficiencies. Indoor and outdoor experimentation is done to accurately assess the performance enhancement hypothesized by the authors. Furthermore, a comparison is made between the indoor and outdoor results to validate each experiment and draw conclusions. The indoor system results were close to the outdoor experiment, suggesting a performance enhancement with an incremental efficiency rise. Highlights: A solar simulator used to mitigate outdoor conditions. SiC-nanofluid used as a cooling fluid. Nanofluid use for cooling increased the electrical, thermal, and total efficiencies. The stability of nanofluids was examined for an extended period and found to be stable.